Induksi Pembentukan Gaharu Menggunakan Berbagai Media Tanam dan Cendawan Acremonium sp. dan Fusarium sp. Pada Aquilaria crassna - TRIADIATI .; DIANA AGUSTIN CAROLINA; MIFTAHUDIN . (Departemen Biologi, Institut Pertanian Bogor, 2016)
Aquilaria crassna is one of the Aquilaria species that could produce agarwood. agarwood production of A. crassna can be induced by microfungi as an inoculant. Ecological interaction between the host plant, wounding and inoculant in the formation of agarwood has not yet clearly. other factors like the plant ages, plant species, environ- ment also played important roles in the formation of agarwood. This research aimed to determine the influence of the combination between planting media and Acremonium sp. and Fusarium sp. to agarwood quality of Aquilaria crassna. The experiment was consisted of two factors, which were five planting media and two inoculants fungi i.e. Acremonium sp. and Fusarium sp. The observed parameters were the percentage of senescence leaves, color of wood, level of fragrant and terpenoid content. The best agarwood fragrant was produced by the seedlings that were treated with either combination of husk charcoal media enriched with NPK fertilizer and Acremonium sp. or the combina- tion between husk charcoal media enriched with Hoagland modified solution and Fusarium sp.. The darkest color of wood was produced by the seedlings that were treated with combination of husk charcoal media enriched with NPK fertilizer and Acremonium sp., as well as for the same media with Fusarium sp.. during the experiment terpenoid could not be detected from the treated seedlings. Acremonium sp. caused more leave senescence than that of Fusarium sp..